Frequency domain optoacoustic tomography using amplitude and phase - Mohajerani, Pouyan; Kellnberger, Stephan; Ntziachristos, Vasilis (Photoacoustics, 2014)
We introduce optoacoustic tomographic imaging using intensity modulated light sources and collecting amplitude and phase information in the frequency domain. Imaging is performed at multiple modulation frequencies. The forward modeling uses the Green's function solution to the pressure wave equation in frequency domain and the resulting inverse problem is solved using regularized least squares minimization. We study the effect of the number of frequencies and of the bandwidth employed on the image quality achieved. The possibility of employing an all-frequency domain optoacoustic imaging for experimental measurements is studied as a function of noise. We conclude that frequency domain optoacoustic tomography may evolve to a practical experimental method using light intensity modulated sources, with advantages over time-domain optoacoustics. © 2014 The Authors.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Frequency domain techniques; Functional imaging; Optical absorption; Optical imaging; Optoacoustic tomography; Tomographic reconstruction